Effects of Fuel Subsidy Removal and Transportation Fare on School Attendance and Learning Outcome in Mathematics among Secondary School Students in Ilorin, Kwara State - Alanamu , Taoheedat; Olarewaju , Adetunji Kamaldeen; Omolola, Abdulrasheed Mariam (Balai Publikasi Indonesia, 2025)
Fuel subsidy in Nigeria is one of many consumption subsidy programmes of the government, which attempts to lower the fuel cost by providing direct financial support to oil firms, thereby lowering the fuel price for Nigerians. The removal of fuel subsidy by the Nigeria President has inevitably raised the cost of living across the board and inflicted strain on the wider population. Public schools emerged as the predominant choice among the people of Kwara State, with students constituting the largest segment, followed by teachers and parents/guardians. There are significant challenges and barriers linked to transportation expenses, putting their detrimental effects on mathematics education. This study presents critical insights into the impact of fuel subsidy removal and transportation fare on teaching and learning of mathematics in secondary schools in Ilorin, Kwara State. The study employed rigorous statistical methods, including statistical techniques of descriptive statistics of frequencies and percentages to summarize the demographic information along chi-square test, Pearson correlation and regression analysis, to explore the connection between transportation fare and students' attendance in mathematics classes, as well as the impact of fuel subsidy removal on the teaching and learning of Mathematics, It is obtained from the result that removal of fuel subsidy have negative impact on the teaching and learning of Mathematics, showing the impact on different areas of teaching and learning processes.A significant revelation was the prevalence of walking or trekking as the primary mode of transportation to school for approximately 64% of students. It revealed a robust correlation r-value of 0.312, and the rejection of the null hypothesis. Additionally, regression analysis confirmed the significant influence of transportation costs on students' attendance and punctuality along chi-square test.Furthermore, respondents offered valuable insights into potential solutions. While adjusting school timings garnered disagreement, an overwhelming majority favored educational authorities providing subsidies for transportation. Respondents also expressed enthusiasm for implementing shuttle services and developing online resources for mathematics learning, particularly in mitigating the impact of transportation barriers.Crucially, the study unearthed significant challenges and barriers linked to transportation expenses, affirming their detrimental effects on mathematics education in selected secondary schools in Ilorin. The findings suggest the provision of urgent strategic interventions, including financial support and digital resources, to alleviate transportation-related barriers and enhance mathematics education